The Influence Of Linkaja's Sawadee Krub Advertisement On Consumer Perception - Alwan Setiawan; Indria Angga Dianita (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract The growth of e-wallet in Indonesia is very rapid, this makes e-wallet an important payment tool demanded by the people. One of the e-wallet is Linkaja. LinkAja uses marketing communication tools to promote their products, which is advertising. LinkAja released an ad titled Sawadee krub on February 13, 2022. This ad attracted 1,410,681 viewers on official Youtube and the feedback in comments was quite positive. This research was conducted with the aim of knowing how much influence Sawadee Krub Linkaja Advertisement on Consumer Perception. This study uses independent variable, namely Advertising with sub-variables Empathy, Persuasion, Impact, and Communication. This study uses dependent variable, namely Consumer Perception with sub-variables Stimulus, Registration, and Interpretation. This research conducted using quantitative methods with descriptive research. The sampling technique is probability sampling, with simple random sampling, and the analysis technique uses normality test, heteroscedasticity test, correlation coefficient test, coefficient of determination, simple linear regression, and hypothesis testing using T test. Based on the results it was found Sawadee Advertisement Krub Linkaja has an influence on consumer perceptions of 73.2%, and 26.8% is influenced by other factors not examined in this study. Keywords: Advertising, Linkaja, Consumer Perception